Earnings Management Factors In The Consumer Goods Industry During The Covid-19 Pandemic - Nur Azizah; Ratna Mappanyukki (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2023)
The global proliferation of the Covid-19 pandemic has adversely impacted public health, society, and the economy. To face the pandemic, managers are frequently required to make highly complicated decisions about financial reports. Earnings management occurs when managers modify financial statements for the advantage of stakeholders by evaluating opportunities in certain business activities. This paper investigates the impact of audit opinion and tax incentives on earnings management and leverage as a moderating variable among consumer goods manufacturing companies. A purposive sampling technique was performed to select 15 manufacturers in the consumer goods industry subsector listed on the Indonesia Stock Exchange between 2019 and 2021, which matched the research criteria. This study's findings indicate that audit opinion and tax incentives influence earnings management among consumer goods companies in the COVID-19 pandemic era. Moreover, leverage was a moderating variable for audit opinion and earnings management, but it did not moderate the effect of tax incentives on earnings management.